Iron Age hillfort defences and the tactics of sling warfare - Robertson, Peter, 1949 November 26- (Archaeopress, 2016)
Sling accuracy at a hillfort is measured here for the first time, in a controlled experiment comparing attack and defence across single and developed ramparts.